Mechanismen und Funktionen von bakteriellen AAA+Entfaltungsmaschinen - Mogk, Axel (Biospektrum, 2021)
Bacterial AAA+ proteins play crucial roles in proteostasis networks and ensure protein homeostasis during stress conditions. They function as ATP-dependent components of proteolytic complexes degrading misfolded proteins or as disaggregases reactivating aggregated proteins. AAA+ proteins generate an ATP-fueled threading force driving substrate unfolding and translocation. Their central functions in protein quality control qualify them as antibacterial drug target.